Antithrombotic treatment for stroke prevention in atrial fibrillation: The Asian agenda. (15th July 2015) - Chen, Chen-Huan; Chen, Mien-Cheng; Gibbs, Harry; Kwon, Sun U.; Lo, Sidney; On, Young Keun; Rosman, Azhari; Suwanwela, Nijasri C.; Tan, Ru San; Tirador, Louie S.; Zirlik, Andreas
Abstract: Atrial fibrillation (AF) is the most common heart arrhythmia. Untreated AF incurs a considerable burden of stroke and associated healthcare costs. Asians have AF risk factors similar to Caucasians and a similarly increased risk of AF-related stroke; however, with a vast and rapidly ageing population, Asia bears a disproportionately large disease burden. Urgent action is warranted to avert this potential health crisis. Antithrombotic therapy with oral anticoagulants is the most effective means of preventing stroke in AF and is a particular priority in Asia given the increasing disease burden. However, AF in Asia remains undertreated. Conventional oral anticoagulation with warfarin is problematic in Asia due to suboptimal control and a propensity among Asians to warfarin-induced intracranial haemorrhage. Partly due to concerns about intracranial haemorrhage, there are considerable gaps between AF treatment guidelines and clinical practice in Asia, in particular overuse of antiplatelet agents and underuse of anticoagulants. Compared with warfarin, new direct thrombin inhibitors and Factor Xa inhibitors are non-inferior in preventing stroke and significantly reduce the risk of life-threatening bleeding, particularly intracranial bleeding. These agents may therefore provide an appropriate alternative to warfarin in Asian patients. There is considerable scope to improve stroke prevention in AF in Asia. Key priorities include: early detection of AF and identification of asymptomatic patients; assessment of stroke and bleeding risk for all AF patients; evidence-based pharmacotherapy with direct-acting oral anticoagulant agents or vitamin K antagonists for AF patients at risk of stroke; controlling hypertension; and awareness-raising, education and outreach among both physicians and patients. Highlights: Asia bears a disproportionate burden of atrial fibrillation (AF) related stroke. There are gaps between guidelines and practice in stroke prevention in AF in Asia. Anticoagulants are underused in Asian AF patients at high risk of stroke. Direct anticoagulants match warfarin in preventing stroke, but with less bleeding. New oral anticoagulants offer a good alternative to warfarin, especially in Asians.